Didactic Interventions: The Voices of Adult Migrants on Second Language Teaching and Learning in a Rural Area in Chile - Valeria Sumonte Rojas; Lidia Andrea Fuentealba; Giselle Bahamondes Quezada; Susan Sanhueza-Henríquez (MDPI AG, 2024)
Research in Chile, regarding language teaching and learning, has focused on Spanish as a first language (L1). However, due to the growing influx and settlement of non-Spanish-speaking adult migrants, the significance of investigating language education within a second-language (L2)-context has surged. Accordingly, the objective of this study is to examine the implementation of a Spanish language teaching-learning program as an L2 from the learners' perspectives. The ultimate objective is to contribute to the advancement of knowledge in this field within the national framework. This qualitative, descriptive/interpretive study involves 10 adult Haitian migrants who do not speak Spanish and live in a rural area. These participants possess varying educational backgrounds and are situated within a vulnerable context. In pursuit of the objective, two focus groups were convened. The outcomes underscore the pressing need for comprehensive macro-level development, at the governmental level, to address the inclusion of migrants. This entails equipping educators with linguistic proficiency and theoretical and pedagogical expertise for instructing an L2 program. Furthermore, the inclusion of linguistic mediators, a judicious use of the learners' L1 as a pedagogical resource, and the implementation of strategies that cater to individual needs contribute to a more effective and inclusive teaching-learning experience.